2023
DOI: 10.2147/ijgm.s441262
|View full text |Cite
|
Sign up to set email alerts
|

Identification of ADAM23 as a Potential Signature for Psoriasis Using Integrative Machine-Learning and Experimental Verification

Pingping Yao,
Yuying Jia,
Xuewei Kan
et al.

Abstract: Background Psoriasis is a common chronic, recurrent, and inflammatory skin disease. Identifying novel and potential biomarkers is valuable in the treatment and diagnosis of psoriasis. The goal of this study was to identify novel key biomarkers of psoriasis and analyze the potential underlying mechanisms. Methods Psoriasis-related datasets were downloaded from the Gene Expression Omnibus database to screen differential genes in the datasets. Functional and pathway enrich… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…Therefore, modern therapeutic strategies used in psoriasis should take macrophage targeting and modulation into account. Advanced bioinformatic studies followed by validation in imiquimod-treated mice demonstrated that upregulation of ADAM23 metalloprotease in macrophages could be used as a biomarker of psoriasis that is likely involved in its pathogenesis and therefore could also be considered as a predictor of potential targets for biological treatments [98]. Moreover, one can speculate that the expression of ADAM23 enables macrophages to modulate cytokine production by psoriasis-associated effector T cells, as previously shown in the case of dendritic cells [99].…”
Section: Macrophages Drive Cytokine Signaling In Psoriatic Inflammati...mentioning
confidence: 79%
“…Therefore, modern therapeutic strategies used in psoriasis should take macrophage targeting and modulation into account. Advanced bioinformatic studies followed by validation in imiquimod-treated mice demonstrated that upregulation of ADAM23 metalloprotease in macrophages could be used as a biomarker of psoriasis that is likely involved in its pathogenesis and therefore could also be considered as a predictor of potential targets for biological treatments [98]. Moreover, one can speculate that the expression of ADAM23 enables macrophages to modulate cytokine production by psoriasis-associated effector T cells, as previously shown in the case of dendritic cells [99].…”
Section: Macrophages Drive Cytokine Signaling In Psoriatic Inflammati...mentioning
confidence: 79%